Evaluasi Metode Lean Project Management Pada Proyek Pelaksanaan Pembangunan Tangki Premium, ADO, dan RFO di Pertamina RU V Balikpapan - Apriana Intan Permatasari; Anggriani Profita; Suwardi Gunawan (Universitas Medan Area, 2022)
The implementation of construction projects cannot be separated from various obstacles and failures. These obstacles and failures cannot be seen in real terms, but if they continue, their impact will be visible at the end of the project. So that everything in a project that does not add value or can be called a waste of waste. To overcome this, you can use the Lean Project Management method. Based on identification and interviews with the Premium, ADO, and RFO tank construction project parties at Pertamina RU V Balikpapan, wastes that have the potential to arise during project implementation are waiting, defects, and unpropriate processing of the eight existing wastes. Waiting and defects in this project are caused by environmental factors, humans, machines, materials and unappropriate processing caused by human factors. For the evaluation matrix for late arrivals, a value of 42 is obtained, for bad weather a value of 45 is obtained, the value of equipment damage is 39. The possible risk factors that arise during project implementation are determined based on identification and interviews with the project party, namely bad weather conditions, late arrival of materials, K3 (Occupational Health and Safety), equipment damage, rework. Keywords: Fishbone, FMEA, Lean Project Management, Waste